1996
DOI: 10.1002/(sici)1099-0488(19961115)34:15<2635::aid-polb11>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure calorimetric study of plasticization of poly(methyl methacrylate) by methane, ethylene, and carbon dioxide

Abstract: Glass transition in the system poly(methyl methacrylate)/compressed gas was studied as a function of the gas pressure p using a high‐pressure Tian‐Calvet heat flow calorimeter. Measurements were made on PMMA‐CH4‐C2H4, and ;‐CO2 at pressures to 200 atm. All three gases plasticize the polymer leading to depression of the glass transition temperature Tg. Trends in the Tg depression were the same as those reported for the solubility of these gases in PMMA; the higher the solubility the larger the depression in Tg.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 2 publications
(1 reference statement)
3
69
0
1
Order By: Relevance
“…Solubility, diffusion coefficient, and swelling data are the most studied or some combination of them [9,[14][15][16][17][18][19][20][21][22][23]. Less abundant are studies about polymer plasticization induced by gas sorption, the majority of which are based on scanning calorimetry with rather poor results especially in systems that exhibit retrograde vitrification [20,[24][25][26][27]. Very rarely are reported experimental data on heat of sorption in polymer-gas systems [28].…”
Section: Introductionsupporting
confidence: 88%
“…Solubility, diffusion coefficient, and swelling data are the most studied or some combination of them [9,[14][15][16][17][18][19][20][21][22][23]. Less abundant are studies about polymer plasticization induced by gas sorption, the majority of which are based on scanning calorimetry with rather poor results especially in systems that exhibit retrograde vitrification [20,[24][25][26][27]. Very rarely are reported experimental data on heat of sorption in polymer-gas systems [28].…”
Section: Introductionsupporting
confidence: 88%
“…The results shown in Figures 6 and 7 are in agreement with previous studies 20,31,41 which showed that on annealing sPS in the range 120-220°C, the planar mesophase is nucleated first, which then converts into the poorly ordered R′ form. The extent of conversion depends on the annealing temperature and time.…”
Section: Resultsmentioning
confidence: 94%
“…On saturation with CO 2 , both the glass transition and the crystallization events move to lower temperatures, and the glass transition becomes sluggish. The plasticization effect of CO 2 on sPS is similar to those observed in other polymer-CO 2 systems, [28][29][30][31]39 whereas the depression in crystallization temperature is similar to that reported for poly(p-phenylene sulfide)-CO 2 . 35 The depressions in T g and the cold crystallization temperature T c for sPS-CO 2 are plotted against the CO 2 pressure p in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…9 According to the result by Handa et al, the crystallization temperature decreased with increasing pressure of CO 2 . [18][19][20] This effect is explained by plasticization due to CO 2 dissolved in the film. The glass transition temperature (T g ) is depressed and therefore the crystallization occurs at lower temperature.…”
Section: Dependence Of Molecular Structure On Temperaturementioning
confidence: 99%